The diurnal movement pattern of waterbirds in the Kukut area of Lake Songkla, southern Thailand - Galbraith, C A; Pierce, G J; Spray, C J; Robinson, I H (Wildfowl, 1999)
Daily movements by waterbirds, between roosting and feeding areas, were observed in the Thale Sap Non-Hunting area (Lake Songkla, southern Thailand) during summer and autumn 1987. Counts of birds in flight in the summer indicated the presence of more than 4500 Lesser Tree Ducks as compared to approximately 1000 ducks of all species in the autumn. In the autumn, approximately 2000 Little Egrets and Great Egrets and 500 Yellow Bitterns and Cinnamon Bitterns made regular use of a roost close to the lakeside village of Kukut and moved between this roost and feeding areas south of Kukut. Numbers of bitterns and egrets recorded in flight past Kukut peaked at dawn and dusk, whereas terns and ducks were seen throughout daylight hours. Egrets foraged on floating grassmats adjacent to Kukut. Analysis indicated temporary local depression of egret numbers due to the presence of fisherman working in and around the grassmats.